Why early prevention of childhood obesity is more than a medical concern: a health economic approach - Sonntag, Diana (Annals of nutrition & metabolism, 2017)
Background: Childhood overweight and obesity are a non-deniable health concern with increasing economic attention. Summary: International studies provide robust evidence about substantial lifetime excess costs due to childhood obesity, thereby underscoring the urgent need to implement potent obesity prevention programs in early childhood. Fortunately, this is happening more and more, as evidenced by the increase in well-conducted interventions. Nevertheless, an important piece of the puzzle is often missing, that is, health economic evaluations. There are 3 main reasons for this: an insufficient number of economic approaches which consider the complexity of childhood obesity, a lack of (significant) long-term effect sizes of an intervention, and inadequate planning of health economic evaluations in the design phase of an intervention. Key Messages: It is advisable to involve health economists during the design phase of an intervention. Equally necessary is the development of a tailored toolbox for efficient data acquisition.